2000
DOI: 10.1080/08964280009595753
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and Seasonal Effects of Salivary Cortisol

Abstract: Assessments of cortisol levels in saliva have been widely used by both researchers and clinicians as an index of adrenal functioning. Quarterly measurements of morning and evening cortisol levels were determined in a longitudinal study of 147 participants (72 women and 75 men) followed for 1 year each. The analysis of salivary cortisol revealed no significant gender or age differences in the sample. There was a sequence effect in quarterly cortisol values with a progressive decrease in serial measurements, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 22 publications
1
28
1
6
Order By: Relevance
“…However, the human data for cortisol are largely inconclusive. Some studies have reported seasonal differences [89,90,91,92,93], whereas others have failed to do so [94,95,96,97]. Similarly, some studies have reported seasonal differences in DHEAS levels [98,99,100], whereas one study found none [101].…”
Section: Circadian Hormone Rhythms Are Influenced By Photoperiod and mentioning
confidence: 91%
“…However, the human data for cortisol are largely inconclusive. Some studies have reported seasonal differences [89,90,91,92,93], whereas others have failed to do so [94,95,96,97]. Similarly, some studies have reported seasonal differences in DHEAS levels [98,99,100], whereas one study found none [101].…”
Section: Circadian Hormone Rhythms Are Influenced By Photoperiod and mentioning
confidence: 91%
“…Data were collected between September and October 2005, with the short time frame likely to eliminate the effects of circadian rhythm changes associated with seasonal factors. 31 Using the indirect enzyme-linked immunosorbent assay 96 method available with the DRG cortisol detection kit (SLV-2930, DRG instruments, Marburg, Germany), cortisol concentration was calculated in ng/ mL. The SIgA concentration was calculated using the salivary secretory IgA indirect enzyme immunoassay kit (Salimetrics, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Of the 919 survey participants, 367 participated in the clinical component of the study, a substantially larger number than the 200 initially anticipated. Each participant was provided with a saliva sample collection kit (Sarstedt Corp., Montreal, Canada) with stepwise instruction for collecting saliva samples adapted from sample collection procedures described in the literature (King et al 2000). Participants were instructed to collect saliva samples over 2 consecutive days and were asked to store the samples in their home freezer or refrigerator.…”
Section: Methodsmentioning
confidence: 99%